Dependency between local carotid arterial stiffness and the presence of atherosclerotic plaque in the carotid basin in hypertensive patients with type 2 diabetes mellitus - Syvolap, V. V.; Bohun, A. O. (Zaporozhye Medical Journal, 2024)
Aim. To assess the impact of atherosclerotic plaque (ASP) on the local arterial stiffness of the common carotid arteries (CCA) in patients with stage II hypertension (HTN) in combination with type 2 diabetes mellitus (T2DM). Materials and methods. The study included 37 patients with stage II HTN and T2DM (mean age 60.4 ± 10.7; 66.7 % male). Patients were divided into two groups: 20 individuals with ASP and <50 % stenosis in the carotid basin, 17 without ASP. The study involved a clinical examination, body weight and percentage of adipose tissue (AT) measurements, analysis of lipid and carbohydrate metabolism laboratory parameters, echocardiography, CCA ultrasound examination with the determination of local stiffness and intima-media complex thickness (IMT). Statistical analysis was performed, significant differences were considered at p < 0.05. Results. The whole-body AT percentage <39.51 % increases the odds ratio (OR) of ASP by 6 times (p = 0.02), an exceeding compliance coefficient (CC) over 0.68 mm2/kPa – by 12.7 times (p = 0.02), right CCA-IMT of over 639 µm – by 1.012 times (p = 0.001), and the factors are mutually reinforcing in the multivariate models and independent of age, sex, body mass index, and glycated hemoglobin level. Ascending aorta dilatation of over 3.34 cm increases the OR of ASP by 11.6 times (p = 0.0107); the factor is enhanced after adjusting for elevated total cholesterol levels over >6.35 mmol/l (p = 0.036) and independent of age and sex. A greater left CCA diameter of more than 8.59 mm (p < 0.019) and right CCA diameter of more than 8.1 mm (p < 0.0001) increases the OR of ASP by 3.7 times (p = 0.001) and 6.6 times (p = 0.0013), respectively, the factor influence increases after adjusting for elevated total cholesterol levels over >6.35 mmol/l (p = 0.031) and it is also unaffected by age and sex. Conclusions. In individuals with stage II HTN and T2DM, the presence of CA atherosclerosis with stenosis up to 50 % is associated with a significantly increased CCA and ascending aorta diameter, a decreased percentage of AT, and an increased compliance coefficient of plaque-free wall segments.